2020
DOI: 10.15611/aoe.2020.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Gender unemployment in the Czech and Polish labour market

Abstract: Making use of EU-Labour Force Survey data, the authors estimated logistic regressions with a maximum likelihood method and found that gender unemployment risk was largely explained by human capital, marital status, receiving financial support, job experience and gender discrimination in both Poland and the Czech Republic. The gender unemployment risk gap amounted to 8% and 10% in Poland and the Czech Republic, respectively. Although the impact of marital status was significant and considerable, married women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…They find that education plays a role especially for female selection into employment and for highly educated women means the reduction of occupational segregation (or desegregation). Similar conclusions were formulated by (Ryczkowski and Zinecker 2020) based on the research covering gender unemployment in the Czech and Polish labor market, who indicated that higher education improves primarily the situation of women. They stated that women in Poland with a master level of education had their unemployment risk lowered by 37% (men: 27%) and in the Czech Republic by 44% (men: 33%).…”
Section: Knowledge Education and Vocational Training Systemssupporting
confidence: 71%
“…They find that education plays a role especially for female selection into employment and for highly educated women means the reduction of occupational segregation (or desegregation). Similar conclusions were formulated by (Ryczkowski and Zinecker 2020) based on the research covering gender unemployment in the Czech and Polish labor market, who indicated that higher education improves primarily the situation of women. They stated that women in Poland with a master level of education had their unemployment risk lowered by 37% (men: 27%) and in the Czech Republic by 44% (men: 33%).…”
Section: Knowledge Education and Vocational Training Systemssupporting
confidence: 71%
“…Ref. [14]- [16] concluded that education and gender affect the employment status of the educated population in Indonesia. Other studies by [17]- [19] highlighted age as factor of unemployment.…”
Section: Methodsmentioning
confidence: 99%
“…Given the binary nature of the dependent variable (losing job or not) we used logistic regression to assess the impact of personal characteristics on gender-biased unemployment in South Africa. Logistic regressions and odds ratios have been a popular technique for unemployment studies where the dependent variable was binary and factors relating to the unemployment status have been assessed [31][32][33][34]. Logistic regression estimates the probability of an event occurring.…”
Section: Methodsmentioning
confidence: 99%